SNPSTRs: Empirically Derived, Rapidly Typed, Autosomal Haplotypes for Inference of Population History and Mutational Processes - Mountain, Joanna L.; Knight, Alec; Jobin, Matthew; Gignoux, Christopher; Miller, Adam; Lin, Alice A.; Underhill, Peter A.

(untitled) (Genome Research, 2002)
Each independently evolving segment of the genomes of a sexually reproducing organism has a separate history reflecting part of the evolutionary history of that organism. Uniparentally or clonally inherited DNA segments such as the mitochondrial and chloroplast genomes and the nonrecombining portion of the Y chromosome have provided, to date, most of the known data regarding compound haplotypic variation within and among populations. These comparatively small segments include numerous polymorphic sites and undergo little or no recombination. Recombining autosomes, however, comprise the major repository of genetic variation. Technical challenges and recombination have limited large-scale application of autosomal haplotypes. We have overcome this barrier through development of a general approach to the assessment of short autosomal DNA segments. Each such segment includes one or more single nucleotide polymorphisms (SNPs) and exactly one short tandem repeat (STR) locus. With dramatically different mutation rates, these two types of genetic markers provide complementary evolutionary information. We call the combination of a SNP and a STR polymorphism a SNPSTR, and have developed a simple, rapid method for empirically determining gametic phase for double and triple heterozygotes. Here, we illustrate the approach with two SNPSTR systems. Although even one system provides insight into population history, the power of the approach lies in combining results from multiple SNPSTR systems.[Supplemental material is available online at http://www.genome.org. The following individual kindly provided reagents, samples, or unpublished information as indicated in this paper: L. Luca Cavelli-Sforza.]